A broadband LNA and mixer for digital video broadcasting applications using a 0.18-m CMOS process - Qiang, Tian; Kim, Eun Seong; Wang, Cong; Park, Min Chul; Kim, Nam Young (WILEY, 2015)
In this study, a broadband low noise amplifier (LNA)/mixer for digital video broadcasting-satellite receiver tuner was fabricated by a 0.18-mu m complementary metal oxide semiconductor (CMOS) process. The proposed broadband LNA receives positive feedback and incorporates a single-ended differential converter to mixer. Two attenuators are used to obtain good noise performance and high linearity. Moreover, the designed CMOS LNA/mixer achieved gain controls in 3-dB steps, an input second-order intercept of 1.37 dBm, and an input third-order intercept of -3.6 dBm in high-gain low-frequency mode. The 6.4-dB noise of LNA was achieved in the frequency range of 950-2150 MHz. The circuit consumes a total current of 25 mA at a supply voltage of 1.8 V and the chip area of the LNA and the mixer are 0.8 x 0.53 mm(2) and 0.8 x 0.6 mm(2), respectively. (c) 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:2092-2099, 2015